Post-exposure treatment with the oxime RS194B rapidly reactivates and reverses advanced symptoms of lethal inhaled paraoxon in macaques. (1st September 2018) - Rosenberg, Yvonne J.; Wang, Jerry; Ooms, Tara; Rajendran, Narayanan; Mao, Lingjun; Jiang, Xiaoming; Lees, Jonathan; Urban, Lori; Momper, Jeremiah D.; Sepulveda, Yadira; Shyong, Yan-Jye; Taylor, Palmer
Highlights: Macaque model to demonstrate clinical symptoms following inhaled or ingested insecticide. Efficacy of blood-brain penetrant RS194 B oxime as a post exposure treatment. Rapid reactivation of paraoxon-inhibited AChE and BChE in blood by RS194 B. Rapid reversal of paraoxon-induced advanced clinical symptoms by RS194B. Abstract: Fatalities from organophosphate (OP) insecticide result from both occupational and deliberate exposure; significantly impacting human health. Like nerve agents, insecticides are neurotoxins which target and inhibit acetylcholinesterases (AChE) in central and peripheral synapses in the cholinergic nervous system. Post-exposure therapeutic countermeasures generally include administration of atropine with a pyridinium aldoxime e.g. pralidoxime, to reactivate the OP-inhibited AChE. However, commonly used oximes inefficiently cross the bloodbrain barrier and are rapidly cleared and their benefit is debated. Recent findings have demonstrated the ability of a novel zwitterionic, centrally acting, brain penetrating oxime (RS194B) to reverse severe symptoms and rapidly reactivate sarin-inhibited AChE in macaques, but it has not been tested following OP pesticide poisoning. In the present study, the symptoms following a lethal dose of inhaled paraoxon (100 ug/kg), were shown to mimic those in insecticide poisoned individuals and were also rapidly reversed in macaques by post-exposure IM administration of 80 mg/kg of RS194B. This occurred with a concomitant reactivation of AChE to 40–100% in < 1 hr and BChE (40% in 8 h). These findings will be used to develop a macaque model with RS194 B as a post-exposure treatment for insecticide poisoning and generate efficacy data for approval under the FDA Animal rule.